1995
DOI: 10.4141/cjps95-137
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance of Hordeum and Brassica species during germination and early seedling growth

Abstract: The deleterious effects of salinity on plant growth are attributed to a decrease in osmotic potential of the growing medium, specific ion toxicity and nutrient ion deficiency (Greenway and Munns 1980). The extent of plant growth depression under saline conditions varies with salt composition, salt concentration, the physiological stage of the plant when it is exposed to salinity, and the plant species (Sharma 1983).Inhibition of seed germination by salinity has been attributed to osmotic effects in barley cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 10 publications
10
64
0
4
Order By: Relevance
“…Son rôle comme agent osmotique a été rapporté par plusieurs auteurs (Kramer, 1983 ;Bewley & Black, 1994). La diminution de la croissance racinaire peut être expliquée par la subérisation des racines soumises au stress hydrique (Huang & Reddman, 1995 ;Kefu et al, 2003). En revanche, il est reconnu que la résistance des végétaux à la sécheresse dépend du degré d'exploitation du sol par le système racinaire.…”
Section: Résultats Et Discussionunclassified
“…Son rôle comme agent osmotique a été rapporté par plusieurs auteurs (Kramer, 1983 ;Bewley & Black, 1994). La diminution de la croissance racinaire peut être expliquée par la subérisation des racines soumises au stress hydrique (Huang & Reddman, 1995 ;Kefu et al, 2003). En revanche, il est reconnu que la résistance des végétaux à la sécheresse dépend du degré d'exploitation du sol par le système racinaire.…”
Section: Résultats Et Discussionunclassified
“…Measures of water relations, however, indicated that salinity imposed a smaller osmotic effect on wild mustard compared with canola. Wild mustard also showed consistently greater tolerance to all osmotic conditions tested, up to -0.9 MPa during germination and early seedling growth stages (Huang and Redmann 1995b). Andersen and Ralston (1989) found that wild mustard, along with several other weedy species tested, did not require aeration when grown for a 4-wk period in nutrient solution; growth was comparable to plants grown in soil.…”
Section: Growth and Developmentmentioning
confidence: 99%
“…Salinity stress can affect seed germination through osmotic effects (Welbaum et al,1990). Salt induced inhibition of seed germination could be attributed to osmotic stress or to specific ion toxicity (Huang and Redmann, 1995). Germination percentage also significantly decreased as the level of salinity of the medium increased (Gulzar et al, 2001;Mauromicale and Licandro, 2002).…”
Section: Discussionmentioning
confidence: 99%